Characterization of Micronutrients, Bioaccessibility and Antioxidant Activity of Prickly Pear Cladodes as Functional Ingredient - Meriam Missaoui; Isabella D’Antuono; Massimiliano D’Imperio; Vito Linsalata; Sadok Boukhchina; Antonio F. Logrieco; Angela Cardinali (Molecules, 2020)
The Opuntia ficus indica (L.) (OFI) is used as a nutritional and pharmaceutical agent in various dietary and value added products. This study underlines the possible use of native prickly pear cladode powder as a functional ingredient for health-promoting food production. To summarise, chemical characterization of polyphenols, minerals and soluble dietary fibre was performed; furthermore, the antioxidant activity and bioaccessibility of polyphenols and minerals were assessed. Eleven compounds between phenolic acids and flavonoids were identified, with piscidic acid and isorhamnetin derivatives being the most abundant. Opuntia’s dietary fibre was mainly constituted of mucilage and pectin, and was composed of arabinose, galactose, glucose, mannose, rhamnose, and xylose sugars. The polyphenols’ bioaccessibility was very high: piscidic acid at 200%, eucomic and ferulic acids >110% and flavonoids from 89% to 100%. The prickly pear cladode powder is also a source of minerals, as cations (calcium, sodium, potassium and magnesium) and anions (sulphate and chloride), with high magnesium bioaccessibilty (93%). OFI powder showed good capacity of radical scavenging measured by DPPH and ABTS methods, with 740 and 775 μmol Trolox/100 g OFI, respectively. Finally, the presented results allow the consideration of this natural product as a source of several essential nutrients, with a possible use in the food industry as a functional ingredient.